Differential responses of soil ammonia-oxidizing archaea and bacteria to temperature and depth under two different land uses. (May 2018) - Lu, Xinda; Nicol, Graeme W.; Neufeld, Josh D.
Abstract: Although soil nitrification has been studied intensively, with an effort to elucidate the relative contributions of both ammonia-oxidizing archaea (AOA) and bacteria (AOB), their relative contributions to N2 O production remain unclear. Understanding the temperature- and depth-dependent activities of AOA and AOB, as well as production of N2 O, is of great importance for predicting their responses to climate change. This work applied the recently discovered AOB inhibitor, octyne, to soil microcosms incubated at different temperatures (20, 30, 40 °C) in order to differentiate ammonia-oxidation potential and N2 O production by AOA and AOB, in soils from different land uses and depth. Our results showed that surface soils (0-15 cm) possessed significantly greater ammonia oxidation potential than subsurface soils (30-45 cm) at all temperatures tested, and that AOA-associated nitrification potential dominated at higher temperatures for both summer and autumn soils. The accumulation of N2 O was only detected in surface agricultural soil at 30 °C and positively correlated with nitrite accumulation within the incubation period. The detected N2 O production, along with most nitrification potential activity, were attributed to AOB, implicating AOB as major producers of this greenhouse gas in the tested agricultural soil. Higher ammonia-oxidation activity and N2 O production within surface agricultural soil reinforces the importance of agricultural surface soils as sources of nitrification and N2 O production, with potential implications for land management practices and responses to climate change. Highlights: Activities of ammonia-oxidizing archaea and bacteria were determined with 1-octyne. Ammonia-oxidizing archaea dominated ammonia oxidation at higher temperatures. Ammonia-oxidizing bacteria dominated N2 O production in surface agricultural soil. Surface agricultural soil was a source of nitrification-associated N2 O production.